Maternal and paternal Age and Risk of Autism Spectrum Disorder (ASD) in Banyumas District, Central Java, Indonesia - Desiyani Nani; Saryono Saryono; Arif Imam Hidayat; Dyla Annisa Putri; Lantip Rujito (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Introduction: The prevalence of autism spectrum disorders has increased in the last three decades. The genetic etiological component of ASD is quite strong and complex. Although genetic factors clearly contribute to ASD risk, environmental, prenatal and post-natal factors are also involved. Father's age and mother's age at the conception of children contribute to the occurrence of autism spectrum disorders in children.Objective: To explore the association between maternal and paternal age and risk of autis, spectrum disorders (ASD) in Banyumas district, Central Java, IndonesiaMethods: An analytical study with case control approach was conducted. This study used case control method that include 43 children with ASD as case group and 189 normal children as control group. Consecutive cases were selected over 4 months, with every weekend allocated to visit the school of children with special needs. Controls were selected from normal children who came with their parents and were also visited by our team at local schools, until the required sample size was reached.Results: This study showed that paternal and maternal age at conception onset were not associate with the occurence of asutism spectrum disorders in children based on the statistical annalyzes in every range of paternal and maternal age results p value > 0,05.Conclusion: Paternal and maternal age were not related with the occurence of autism spectrum disorders